Local and Lower Limb Complications during and after Femoral Cannulation for Extracorporeal Life Support - Kreibich, Maximilian; Benk, Christoph; Leitner, Sophie; Beyersdorf, Friedhelm; Morlock, Julia; Scherer, Christian; Rylski, Bartosz; Trummer, Georg (The Thoracic and Cardiovascular Surgeon, 2019)
Objective The extracorporeal life support system (ECLS) system is a lifesaving option for patients in pulmonary and/or cardiac failure. We reviewed our data on local complications in the leg and groin during and after ECLS explantation.Methods Patients were included when an ECLS was cannulated in the groin and the ECLS was successfully weaned and explanted. Data were collected retrospectively in patients from January 2013 to January 2016.Results In this study, 90 patients were included; 39 (43%) ECLS were implanted with surgical cut down and 51 (57%) ECLS were implanted percutaneously. Most patients needed ECLS support following cardiac surgery: cut down: 25 (64%) versus percutaneous: 28 (55%) (p = 0.40). A distal leg perfusion cannula was implanted simultaneously in 61 (68%) patients (cut down: 25 [64%] vs. percutaneous: 36 [71%], p = 0.36). Distal leg ischemia was diagnosed in a total of 10 (11%) patients (cut down: 2 [5%] vs. percutaneous: 8 [16%], p = 0.18). Of those 10 patients, 5 patients had leg ischemia despite a distal leg perfusion cannula in place (cut down: 1 [3%] vs. percutaneous: 4 [8%], p = 0.38). Revascularization was successfully achieved in all patients and no amputations had to be performed. Similar rates of wound healing disorders were observed in both groups: cut down: 11 (28%) versus percutaneous: 10 (20%) patients (p = 0.45).Conclusion Surgical and percutaneous implantation and explantation of ECLS are safe and feasible with comparable complication rates, including wound healing disorders. We recommend that a lower limb perfusion cannula should be placed to prevent leg ischemia. Surgical cut-down placement of the distal leg perfusion cannula may reduce the incidence of distal leg ischemia compared with percutaneous distal leg cannula implantation. Correct placement of the cannula should be controlled.
Keywords: extracorporeal life support; ECLS; intensive care; peripheral vascular disease; surgery; complications; wound healing